Discrimination and Classification of Poultry Feeds Data - A.A, Olosunde; A.T, Soyinka (International Journal of Mathematical Research, 2013)
This study is aimed at employing discriminant analysis method and classification for the purpose of achieving the assessment of a discriminant function through which we can discover the reasons of the actual difference between two groups of eggs of which the chicken were fed with different combination of feeds. Fisher’s Linear Discriminant Function (LDA) was used as a tool for the Statistical analysis. It was estimated on the basis of a sample of 96 chickens, which were classified into two groups of 48 chickens each. One group was fed with in-organic copper salt combination while the second group with organic copper salt combination. Some important attributes are measured from the eggs produced from these two groups; such as egg’s size(g) and cholesterol level(mg).The results obtained assert the efficiency of the discriminant function which we obtained and the possibility of its use for the purpose of discriminating and classifying the eggs of unknown feeds into corresponding group in future.